Modern approaches for the course of medical rehabilitation of physical culture in elderly patients with gonarthrosis - Y.I. Shramko; T.A. Zhmurova (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The effect of the complex exercise using static stretching along the axis of voluntary rehabilitation for elderly patients with gonarthrosis. The study involved 20 elderly women suffering from bilateral gonarthrosis 1-2 stages. Noted a more pronounced beneficial effect of locomotor functions and physical performance patients compared with conventional methods. The main group indicator function improving lower extremity and the Leken index exceeded those of the control group by 50%. Also significantly increased quadriceps muscle force in patients on the basis of 33.3% on the right and 25% left. Indicators extension in the knee joints in the study group achieved a 12% larger values than those in the control group. In the main group was significantly increased exercise performance by 32.6% as compared to the control group and reached the lower limit of the age norm.